Regional deterrence and 'non-genuine' refugees: The punitive legacy of the 1989 Comprehensive Plan of Action. (June 2019) - Loughnan, Claire
The outsourcing of refugee protection obligations is reshaping state relations in the Asia Pacific and Southeast Asian region and has underscored a progressively punitive approach to 'irregular' refugee movement. Such a shift can be partially but importantly traced to the deterrent foundations of Australia's dual-track processing system, introduced as an outcome of the 1989 Comprehensive Plan of Action on Indochinese Refugees (CPA). Although the CPA was a multilateral attempt to improve access to refugee protection through a coordinated regional response, in many respects it undermined the potential for refugee protection. By examining the history and motivations of regional responses, we can trace their impact as an exercise in either affirming or disavowing regional responsibility for refugee protection, while enabling some states to retain and even increase their capacity for control in the region. Given the call by the Global Compact on Refugees for coordinated regionally responsive approaches based on humanitarian principles, the crafting of regional and global plans, their motives and their governing logic, require ongoing and careful attention to ascertain the forms of responsibility or irresponsibility for refugee protection which they might sustain over time.